Synthesis, characterization and antibacterial activity of hybrid chitosan-cerium oxide nanoparticles: As a bionanomaterials - Senthilkumar, R.P.; Bhuvaneshwari, V.; Ranjithkumar, R.; Sathiyavimal, S.; Malayaman, V.; Chandarshekar, B. (International journal of biological macromolecules, 2017)
•Hybrid chitosan cerium oxide nanoparticles prepared for the first time by using natural Sida acuta leaf extract. The FTIR spectrum of prepared samples showed the formation of CeO bonds and chitosan main chains COC and CO respectively.•XRD pattern revealed that hybrid Chi-CeO2 NPs have a polynanocrystalline structure with fluorite cubic phase.•TEM image shows that prepared hybrid ChiCeO2 NPs are spherical in shape with average particles size various from 3.61nm to 24.40nm.•FESEM images explained interaction of hybrid ChiCeO2 NPs on the membrane surface changes of test pathogens. The hybrid chitosan cerium oxide nanoparticles were prepared for the first time by green chemistry approach using plant leaf extract. The intense peak observed around 292nm in the UV–vis spectrum indicate the formation of cerium oxide nanoparticles. The XRD pattern revealed that the hybrid chitosan-cerium oxide nanoparticles have a polycrystalline structure with cubic fluorite phase. The FTIR spectrum of prepared samples showed the formation of Ce-O bonds and chitosan main chains COC and CO. The FESEM image of hybrid chitosan cerium oxide nanoparticles revealed that the particles are spherical in shape with grains size varying from 23.12nm to 89.91nm. EDAX analysis confirmed the presence of Ce, O, C and N elements in the prepared sample. TEM images showed that the prepared hybrid chitosan-cerium oxide nanoparticles are predominantly uniform in size and most of the particles are spherical in shape with less agglomeration and the particles size varies from 3.61nm to 24.40nm. The prepared chitosan cerium oxide nanoparticles of 50μL concentration showed good antibacterial properties against test pathogens, which was confirmed by the FESEM analysis. The prepared small particle size facilitate that these hybrid ChiCO2 NPs could effectively be used in biomedical applications.